Etnoekologi Sistem Pengelolaan dan Teknologi Pertambangan Minyak Tradisional di Desa Wonocolo - Muhammad Azra Fikri Maulana; Harto Wicaksono (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
Oil mining in Wonocolo Village, Bojonegoro Regency, uses simple technology that can be viewed from an ethnoecological perspective. Although the technology applied is relatively simple, mining activities still cause negative impacts on the environment. However, community knowledge about environmental management can reduce these impacts. The research method used was qualitative with an observation, interview and literature study approach, involving the village head, mine workers, mine owners and the surrounding community. The results showed that the community has a deep understanding of the ecosystem and oil mining practices. They try to maintain the balance of nature through developed customary norms, such as planting trees and soaking wells after use. This practice reflects the concept of ethnoecology, in which the community tries to maintain harmony between the natural and social environment. This high ecological awareness indicates the important role of local traditions in reducing the negative impacts of mining activities.